Improving the quality of online English teaching and learning at universities and colleges - Nguyen Thu Huong (Journal of State Management, 2025)
In the context of digital transformation and deep international integration, online teaching and learning have become an inevitable trend in higher education. For English language courses, online learning not only enables students to be more flexible in managing their study time and learning environment but also creates opportunities to incorporate modern technologies into language skill development. However, this form of teaching and learning still faces several limitations regarding teaching methodology, technological infrastructure, and interaction between lecturers and students. This article reviews the current situation based on previous studies and, on that basis, proposes several solutions to improve the quality of online English teaching and learning at universities and colleges.